Locations of GPS-collared moose and geographic correlates, as well as for random points within study area - Harris, Richard; Burkholder, Braden; DeCesare, Nicholas; Boccardori, Vanna; Garrott, Robert (Zenodo, 2022)
Moose are among the many species that are vulnerable to both direcdt and indirect effects of climate change. Habitat selection is one framework to assist investigators in disentangling the various factors (including weather) that ultimately dictate how animals respond to their environment. We investigated patterns of winter habitat selecdtion by adult female moose in southerwestern MOntana, USA, during 2007-2010, and how that selection was affected by snow (quantified by snow water equivalent) and winter temperatures. We used data from GPS colalrs and a suite of environmental covariates to quantify winter habitat selection at both study area (2nd order) and home range (3rd order) spatial scales using resource selection functions. Moose strongly select for the willow ( Salix spp.) cover type, and against grassland cover. Moose use of conifer cover at the home range scale increased when either amount of snow or ambient temperature was higher, altough the latter only during periods of the day when conifer pathces were likely to have been cooler than cover types lacking a canopy. Wildlife conservatoin and management naturally focuses on preferred habitats, particularly those that fulfill essentially all forgaing requirements. However, habitats used preferentially under stresful weather conditions, even if used rarely overall, can also form a critical part of a species' overall needs., Funding provided by: Montana Fish, Wildlife and Parks* Crossref Funder Registry ID: Award Number: